2021
DOI: 10.3389/fcell.2021.712196
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Classifier Based on Urinary Proteomics for Distinguishing Between Benign and Malignant Ovarian Tumors

Abstract: BackgroundPreoperative differentiation of benign and malignant tumor types is critical for providing individualized treatment interventions to improve prognosis of patients with ovarian cancer. High-throughput proteomics analysis of urine samples was performed to identify reliable and non-invasive biomarkers that could effectively discriminate between the two ovarian tumor types.MethodsIn total, 132 urine samples from 73 malignant and 59 benign cases of ovarian carcinoma were divided into C1 (training and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…This has given rise to the hope that urinary protein discovery may be useful for early disease diagnosis, determining the choice of treatment regime and monitoring its effects, keeping track of the disease state, and also assess its prognosis . Urine samples have been widely appreciated as a biofluid for the diagnosis of a range of disorders including infections, neurological disorders, hormone-dependent changes, genetic disorders, and cancer. , …”
Section: Urine As An Accessible Biological Fluid For Diagnosing Infec...mentioning
confidence: 99%
See 1 more Smart Citation
“…This has given rise to the hope that urinary protein discovery may be useful for early disease diagnosis, determining the choice of treatment regime and monitoring its effects, keeping track of the disease state, and also assess its prognosis . Urine samples have been widely appreciated as a biofluid for the diagnosis of a range of disorders including infections, neurological disorders, hormone-dependent changes, genetic disorders, and cancer. , …”
Section: Urine As An Accessible Biological Fluid For Diagnosing Infec...mentioning
confidence: 99%
“…8 Urine samples have been widely appreciated as a biofluid for the diagnosis of a range of disorders including infections, 9 neurological disorders, 10 hormone-dependent changes, 11 genetic disorders, 12 and cancer. 13,14 Urine is the second most frequent clinical specimen after blood in clinical and hospital-based diagnostic settings. The three major urinary sample assessments include the visual appearance, chemical composition study, and microbial examination.…”
Section: History Of Othermentioning
confidence: 99%
“…As demonstrated by clinical investigations, HE4 is recognized as a promising biomarker of ovarian carcinoma . To date, several common methods have been widely applied for quantitative analysis of HE4, including enzyme-linked immunosorbent assay (ELISA), fluorescence (FL), and mass spectrometry (MS) . Recently, electrochemical (EC) and photoelectrochemical (PEC) techniques have attracted extensive attention in sensitive bioassays of biomarkers for early diagnosis and therapy of cancers in clinic due to their distinct advantages (e.g., easy portability, low background noise, simple operation, high sensitivity, and good reproducibility) .…”
Section: Introductionmentioning
confidence: 99%
“…5 To date, several common methods have been widely applied for quantitative analysis of HE4, including enzyme-linked immunosorbent assay (ELISA), 6 fluorescence (FL), 7 and mass spectrometry (MS). 8 Recently, electrochemical (EC) and photoelectrochemical (PEC) techniques have attracted extensive attention in sensitive bioassays of biomarkers for early diagnosis and therapy of cancers in clinic due to their distinct advantages (e.g., easy portability, low background noise, simple operation, high sensitivity, and good reproducibility). 9 Strikingly, combining the advantages of PEC and EC technologies to construct dual-mode biosensors (based on two different response mechanisms and relatively independent signal transduction) can greatly improve the accuracy of quantitative analysis and correct the systematic errors and background signals of the single-mode readout sensing platform.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This approach has been used in the treatment and research of a variety of diseases such as pulmonary fibrosis [16] , colitis [17] , glioma [18] and other diseases. Studies have shown that urine biomarkers can classify diseases such as predicting chronic kidney disease (CDK) [19] and distinguishing benign and malignant ovarian cancer [20] . Urine biomarkers can also be used to detect whether complete resection and recurrence occur after tumor surgery so that adjustments can be made in time to reduce the risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%